2012
DOI: 10.1021/jp305470j
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Action Spectroscopy of Iodine Labeled Peptides and Proteins in the Gas Phase

Abstract: Structural investigations of large biomolecules in the gas phase are challenging. Herein, it is reported that action spectroscopy taking advantage of facile carbon-iodine bond dissociation can be used to examine the structures of large molecules, including whole proteins. Iodotyrosine serves as the active chromophore, which yields distinctive spectra depending on the solvation of the side chain by the remainder of the molecule. Isolation of the chromophore yields a double featured peak at 290 nm, which becomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…[35][36][37] Kirk et al recently demonstrated the wavelength dependence of iodine atom loss from iodo-tyrosines by photodissociation (PD) action spectroscopy, highlighting the influence of charge state on the efficacy of photoproduct formation. 38 Compared with CID, photodissociation of aryl iodides facilitates the production of radical sites without complications due to isomerisation. 39,40 Strategies that utilise UV radiation and a photolabile radical precursor show promise for peptide characterisation.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Kirk et al recently demonstrated the wavelength dependence of iodine atom loss from iodo-tyrosines by photodissociation (PD) action spectroscopy, highlighting the influence of charge state on the efficacy of photoproduct formation. 38 Compared with CID, photodissociation of aryl iodides facilitates the production of radical sites without complications due to isomerisation. 39,40 Strategies that utilise UV radiation and a photolabile radical precursor show promise for peptide characterisation.…”
Section: Introductionmentioning
confidence: 99%
“…For biomolecules, and other molecules with suitably facile bonds, a PD action spectrum can provide rich details about the primary molecular structure, electronic excited states and conformation of ions in the gas-phase [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, E(C/T)D techniques yield hydrogen‐rich radical cations of peptides/proteins in multiply protonated forms by adding a low‐energy electron. Hydrogen‐deficient peptide radical cations can also be produced; for example, through photo‐dissociation of protonated peptides derivatized with photo‐labile covalent bonds, under ultraviolet (UV) or vacuum ultraviolet (VUV) irradiation . Peptide dissociation behavior in tert ‐butyl peroxycarbamate–, Vazo 68–, and TEMPO– (2,2,6,6‐tetramethylpiperidine‐1‐oxyl) based FRIPS (free radical–initiated peptide sequencing) MS has been analyzed in both positive‐ and negative‐ion modes for a number of peptides.…”
Section: Common Techniques For Formation Of Peptide Radical Ions In Tmentioning
confidence: 99%